Unveiling the charge transport blockade in the D2 branch of the photosystem II reaction center - Aditya Kumar Mandal; Shubham Basera; William A. Goddard; Prabal K. Maiti (Proceedings of the National Academy of Sciences, 2025)
Photosynthesis, the fundamental process sustaining life on Earth, depends on the photosystem II (PSII) reaction center’s ability to initiate the charge transport process. In this study, we have investigated this charge transport process with a focus on the dissimilarity between the two branches of the PSII reaction center, D1 and D2. Utilizing Marcus theory, we have calculated the reorganization energies and activation barriers for all the key steps involved in the charge transport process. Our analysis reveals that while both D1 and D2 branches exhibit similarities in the initial stages, the rate-determining step in the D2 branch has a significantly higher activation barrier (0.2 eV) than D1 branch (0.1 eV), suggesting a much less favorable energetic landscape. Further, the calculation of current–voltage (I-V) characteristics confirms the higher resistance in the D2 branch compared to the D1 branch, emphasizing its nonconductive nature. This comprehensive approach combining energetic and kinetic considerations provides valuable insights into the asymmetry of charge transport in PSII that may be important in optimizing PSII functionality.